2019
DOI: 10.1016/j.envpol.2018.12.091
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of pollutants sorbed on environmental sample microplastics collected on beaches: Part I-adverse effects on fish cell line

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 63 publications
(80 reference statements)
2
34
0
Order By: Relevance
“…PA, polyamide; PS, polystyrene; PE, polyethylene; PC, polycarbonate; PP, polypropylene; PVC, polyvinylchloride; NPs, nanoplastics (<1 µm); MPs, microplastics. In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes.…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
“…PA, polyamide; PS, polystyrene; PE, polyethylene; PC, polycarbonate; PP, polypropylene; PVC, polyvinylchloride; NPs, nanoplastics (<1 µm); MPs, microplastics. In line with MPs/NPs activity as carriers or vectors of environmental contaminants, studies using fish cell lines have revealed that, while pristine plastics show no toxicity, those sampled from different islands around the world do [96], and so do those that have been mixed with human pharmaceuticals [97]. MPs/NPs were shown to modulate the toxicities a range of pollutants/toxicants, including phenanthrene [75], mercury [49], cadmium [46][47][48], polychlorinated biphenyls (PCBs) [98], gold ions [99], and the antibiotic roxithromycin [100], in fishes.…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
“…Overall, Asian countries showed the highest concentrations of PCBs. In Chile, for instance, an average concentration of 39.90 ng/g was reported in the bay of San Vicente (Pozo et al, 2020), and in the Easter Islands, the concentration was <5 ng/g (Pannetier et al, 2019). In Portugal, it can be observed that the mean PCBs concentrations in beach sediments from Fonte de Telha (14.52 ng/g) and Cresmina (13.05 ng/g) are very similar, although they are not geographically close (Frias et al, 2010).…”
Section: Organic Compoundsmentioning
confidence: 99%
“…The authors found if the contaminant was close to equilibrium conditions in microplastics and the environmental medium, accumulation in the fish is not as likely, and suggested future studies focus on plastic additive chemicals that likely exist within plastic particles at higher concentrations than surrounding media. Pannetier et al (2019) used the rainbow trout liver cell line to evaluate toxicity of chemicals sorbed to microplastics collected on beaches around the world. Results indicated that EROD activity was altered depending on the microplastic particle's contaminant profile (e.g., sorbed chemicals and components of the plastic such as additive chemicals) and DNA damage was possible based on results of a comet assay.…”
Section: Fishmentioning
confidence: 99%